2016
DOI: 10.1097/qad.0000000000001199
|View full text |Cite
|
Sign up to set email alerts
|

Reproducing SIVΔnef vaccine correlates of protection

Abstract: Vaccination with SIVmac239Δnef provides robust protection against subsequent challenge with wild type SIV, but safety issues have precluded designing an HIV-1 vaccine based on a live attenuated virus concept. Safe immunogens and adjuvants that could reproduce identified immune correlates of SIVmac239Δnef protection therefore offer an alternative path for development of an HIV vaccine. Here we describe SIV envelope trimeric gp41 (gp41t) immunogens based on a protective correlate of antibodies to gp41t concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…However, a gp41 subunit virosome vaccine regimen that elicited antiviral gp41 specific antibodies did protect nonhuman primates against vaginal SHIV challenges [ 48 ]. Additionally, in a nonhuman primate SIV immunization model, gp41 antibodies concentrated at the mucosa correlated with protection [ 49 , 50 ]. Thus, studies from multiple independent groups employing different strategies of passive infusion and vaccination studies in nonhuman primates have demonstrated the potential of gp41 antibodies to protect.…”
Section: Discussionmentioning
confidence: 99%
“…However, a gp41 subunit virosome vaccine regimen that elicited antiviral gp41 specific antibodies did protect nonhuman primates against vaginal SHIV challenges [ 48 ]. Additionally, in a nonhuman primate SIV immunization model, gp41 antibodies concentrated at the mucosa correlated with protection [ 49 , 50 ]. Thus, studies from multiple independent groups employing different strategies of passive infusion and vaccination studies in nonhuman primates have demonstrated the potential of gp41 antibodies to protect.…”
Section: Discussionmentioning
confidence: 99%
“…Broadly neutralizing antibodies (BNAbs) against HIV-1 are of great interest and encouraging for researchers to prevent and treat AIDS, 1,8,15 however, how to elicit BNAbs by vaccination is still an unraveled question. 27,28 Besides BNAbs, potential correlates of protection also include ADCC antibodies 29 and effective T cell responses. 30,31 Efforts to elicit broadly-directed, codominant responses to conserved epitopes of protective CD4 and CD8 T cell responses have been sustained for many years 10,32,33 although such responses might lead to partial protection from HIV-1 infection, rather than sterile prevention or virus eradication.…”
Section: Discussionmentioning
confidence: 99%
“…The FcRn interacts with the Fc region of IgG and is involved in recycling of IgG within cells. This interaction is also involved in actively transporting IgGs to sites of pathogen encounter [ 96 ]. For example, the M428L and N434S (“LS”) mutations prolong antibody half-life without compromising antigen-binding or other Fc-mediated functions [ 97 ].…”
Section: Main Textmentioning
confidence: 99%
“…In the case of VRC01, the FcRn enhancing mutation VRC01-LS [ 95 ] lead to 2–3 fold higher in vivo half-life in macaques compared to VRC01. In addition, increased and prolonged levels of VRC01-LS were detected in vaginal and rectal mucosal tissue compared to the unmodified VRC01 [ 96 , 97 ]. Recently, Griffin and colleagues showed that a single intramuscular dose of Nirsevimab protected infants for an entire RSV season [ 98 ].…”
Section: Main Textmentioning
confidence: 99%